2016
DOI: 10.1016/j.drugalcdep.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in FAAH is associated with cannabis use disorders in a young adult sample of Mexican Americans

Abstract: Background Cannabis is a commonly used drug and studies have shown that a significant portion of the variation in cannabis use disorders (CUDs) is heritable. Five genes known to play a role in the endocannabinoid system and CUDs were examined in a community sample of young adult Mexican Americans (MAs): CNR1, MGLL, FAAH, DAGLA, and DAGLB. Methods Gene-based tests were run to test for association between each gene and two DSM-5 cannabis phenotypes. Subsequent linear regressions were run in PLINK using an addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
0
18
0
1
Order By: Relevance
“…The underlying mechanisms that dictate why only a fraction of those individuals experimenting with cannabis become dependent remain unknown. Substantial evidence implicates genetic factors mediating the risk for drug dependence, including cannabis use disorder, in susceptible individuals (1,11,13,32). In addition, adolescence, particularly in female mice, represents a highly vulnerable developmental period in which cannabis use predicts a higher risk of dependence compared to adulthood (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms that dictate why only a fraction of those individuals experimenting with cannabis become dependent remain unknown. Substantial evidence implicates genetic factors mediating the risk for drug dependence, including cannabis use disorder, in susceptible individuals (1,11,13,32). In addition, adolescence, particularly in female mice, represents a highly vulnerable developmental period in which cannabis use predicts a higher risk of dependence compared to adulthood (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that FAAH 385C/A polymorphism might play an important role in the pathophysiological process of tolerance, and addiction of METH dependence, and could be used to identify high‐risk individuals. Previous studies revealed that the allele A or carried A genotypes of the FAAH 385C/A polymorphism played a risk role in alcohol dependence and illicit drug abuse, including cannabis, amphetamine, METH, and cocaine (Dlugos et al., ; Filbey et al., ; Melroy‐Greif et al., ; Sim et al., ; Sloan et al., ; Tyndale et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The endocannabinoid system (ECS) was one of the most important neural signaling pathways implicated in substance abuse and dependence, such as modulated brain reward effect, related behaviors, and influenced addiction vulnerability (Morita et al., ; Parsons & Hurd, ). The fatty acid amide hydrolase (FAAH) gene is a membrane‐bound serine hydrolase of the ECS, and may be involved in the pathophysiological process of METH dependence, such as oxidative stress, excitotoxicity, and inflammation (Melroy‐Greif et al., , Moratalla et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Common single nucleotide polymorphisms in or near CNR1 , CNR2 , FAAH and MGLL have been reported to be associated with a variety of clinical phenotypes in candidate gene association studies (substance abuse disorders, cardiovascular disease risk factors, irritable bowel syndrome, migraine, chronic pain and mood disorders) [ 21 30 ]. The effect sizes are generally small, however, and replication studies in larger independent cohorts have been met with mixed results [ 31 35 ]. In contrast, the impact of rare genetic variation in genes associated with the endocannabinoid system has not been studied systematically.…”
Section: Introductionmentioning
confidence: 99%